Phosphinatophenylporphyrins tailored for high photodynamic efficacy. Issue 39 (27th September 2018) - Hynek, Jan; Koncošová, Martina; Zelenka, Jaroslav; Křížová, Ivana; Ruml, Tomáš; Kubát, Pavel; Demel, Jan; Lang, Kamil
Abstract : Porphyrin phosphinates are attractive candidates for photodynamic applications since their cellular uptake can be easily tuned by the substituent on phosphorus atoms. Abstract : The development of effective photosensitizers is particularly attractive for photodynamic therapy of cancer. Three novel porphyrin photosensitizers functionalized with phosphinic groups were synthesized and their physicochemical, photophysical, and photobiological properties were collected. Phosphinic acid groups (R 1 R 2 POOH) attached to the porphyrin moiety (R 1 ) contain different R 2 substituents (methyl, isopropyl, phenyl in this study). The presence of phosphinic groups does not influence absorption and photophysical properties of the porphyrin units, including the O2 ( 1 Δg ) productivity. In vitro studies show that these porphyrins accumulate in cancer cells, are inherently nontoxic, however, exhibit high phototoxicity upon irradiation with visible light with their phototoxic efficacy tuned by R 2 substituents on the phosphorus centre. Thus, phosphinatophenylporphyrin with isopropyl substituents has the strongest photodynamic efficacy due to the most efficient cellular uptake. We demonstrate that these porphyrins are attractive candidates for photodynamic applications since their photodynamic efficacy can be easily tuned by the R 2 substituent.